1989
DOI: 10.1002/1097-0142(19891115)64:10<2053::aid-cncr2820641014>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Radical surgery for gastric cancer. A review of the Japanese experience

Abstract: Overall results after operations for gastric cancer in Japan are far superior to results obtained in the US and Europe. We have reviewed the Japanese literature in an effort to determine what factors explain this difference. It appears that the survival differences are due mainly to a greater frequency of early gastric cancer in Japan; meticulous histopathologic evaluation of the surgical specimens, resulting in more accurate pathologic staging; and the presumed benefit of extended nodal dissection when it ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0
15

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(106 citation statements)
references
References 20 publications
3
88
0
15
Order By: Relevance
“…This is probably owing to a more advanced stage of the tumours in the former site, frequently in pT3 or pT4 at the diagnosis (Hermanek, 1986;Davessar et al, 1990). Furthermore, the extensive distribution of potentially metastatic lymph nodes in advanced cancer of the proximal third may explain the poorer prognosis (Noguchi et al, 1989). In our study, survival rates of the tumours in the middle or distal parts were almost twice as favourable as those in the proximal third (5 year survival 30-35% vs 15% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably owing to a more advanced stage of the tumours in the former site, frequently in pT3 or pT4 at the diagnosis (Hermanek, 1986;Davessar et al, 1990). Furthermore, the extensive distribution of potentially metastatic lymph nodes in advanced cancer of the proximal third may explain the poorer prognosis (Noguchi et al, 1989). In our study, survival rates of the tumours in the middle or distal parts were almost twice as favourable as those in the proximal third (5 year survival 30-35% vs 15% respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cohort studies have highlighted the survival difference in patients with resectable GC between Western and Eastern countries [6][7][8][9][10][11][12][13][14]. Noguchi et al [6] reported a survival difference between high-volume centers in the USA and Japan that was no longer apparent after adjusting for tumor location.…”
Section: Introductionmentioning
confidence: 99%
“…Curative surgery is an essential treatment for the long-term survival of patients with gastric cancer (Noguchi et al, 1989;Shiu et al, 1989;Fuchs and Mayer, 1995). However, the prognosis of patients with locally advanced gastric cancer is generally poor even with curative resection (Noguchi et al, 1989;Shiu et al, 1989;Fuchs and Mayer, 1995).…”
mentioning
confidence: 99%
“…Curative surgery is an essential treatment for the long-term survival of patients with gastric cancer (Noguchi et al, 1989;Shiu et al, 1989;Fuchs and Mayer, 1995). However, the prognosis of patients with locally advanced gastric cancer is generally poor even with curative resection (Noguchi et al, 1989;Shiu et al, 1989;Fuchs and Mayer, 1995). Adjuvant chemotherapy has failed to demonstrate a significant survival benefit for such patients in most randomized trials and meta-analyses, except in a few studies with positive results (Shiu et al, 1989;Krook et al, 1991;Kim et al, 1992;Hermans et al, 1993;Nakazato et al, 1994;Fuchs and Mayer, 1995;Lise et al, 1995;Macdonald et al, 1995;Kelsen, 1996;Kim et al, 1998;Cirera et al, 1999;Earle and Maroun, 1999).…”
mentioning
confidence: 99%